2015
DOI: 10.3109/17435390.2015.1078852
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in DNA methylation corresponding with lung inflammation and as a biomarker for disease development after MWCNT exposure

Abstract: Use of multi-walled carbon nanotubes (MWCNT) is growing which increases occupational exposures to these materials. Their toxic potential makes it important to have an in-depth understanding of the inflammation and disease that develops due to exposure. Epigenetics is one area of interest that has been quickly developing to assess disease processes due to its ability to change gene expression and thus the lung environment after exposure. In this study, promoter methylation of inflammatory genes (IFN-γ and TNF-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 43 publications
5
56
1
1
Order By: Relevance
“…In our study, Thy-1 was significantly hypermethylated in both 10- to 12- and 20-week old offspring of prenatal and early-life ETS-exposed dams. We previously confirmed that Thy-1 hypermethylation in murine lung tissue corresponds to decreased mRNA expression (Brown et al, 2015). Given that Thy-1 was persistently hypermethylated and preceded the apparent onset of adult lung disease (concluded from collagen deposition and histopathology data), we suggest that prenatal and early-life ETS exposure induces latent fibrotic lung disease and that altered Thy-1 expression via promoter hypermethylation is involved in this adult disease process.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our study, Thy-1 was significantly hypermethylated in both 10- to 12- and 20-week old offspring of prenatal and early-life ETS-exposed dams. We previously confirmed that Thy-1 hypermethylation in murine lung tissue corresponds to decreased mRNA expression (Brown et al, 2015). Given that Thy-1 was persistently hypermethylated and preceded the apparent onset of adult lung disease (concluded from collagen deposition and histopathology data), we suggest that prenatal and early-life ETS exposure induces latent fibrotic lung disease and that altered Thy-1 expression via promoter hypermethylation is involved in this adult disease process.…”
Section: Discussionsupporting
confidence: 54%
“…Using the incorporated iCys Workstation computer software (version 3.4) tools, we randomly hand-selected six interstitial areas and six airways for high-resolution scans. “Phantom” contours were used to divide tissues into very small (8-µm diameter) circles as previously described (Brown et al, 2015; Brown et al, 2016). Briefly, a blue staining contour was considered a collagen-positive event via trichrome stain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, more genes were epigenetically altered with AuNPs than with CNTs, in contrast with the paradigm that exposure to AuNPs does not induce an adverse biological response (Tabish et al, 2017). Alterations in DNA methylation, corresponding with lung inflammation, induced by the exposure to MWCNTs in C57BL/6 mice were shown by another group (Brown et al, 2016). In this study, promoter methylation of inflammatory genes (IFNG and TNF) correlated with initial cytokine production.…”
Section: Carbon Nanotubescontrasting
confidence: 56%
“…Aging [23], smoking [24,25], and heavy metal exposure [26,27], acrolein [28,29] have all been associated with changes in the DNA methylome, and with changes in DNMT expression, but the mechanisms by which these changes occur are largely unknown. DNA methyltransferases (DNMTs) such as DNMT1, DNMT3A and DNMT3B contribute to various physiologic and pathologic conditions including embryo implantation [30], cytomegalovirus infection [31], radiation [32], cancer, aging, neural cell differentiation [33].…”
Section: Discussionmentioning
confidence: 99%